The value of economic and cultural capital to college readiness among Filipino senior high school graduates - Editha S. Pagulayan; Jay Emmanuel L. Asuncion; Antonio I. Tamayao; Rudolf T. Vecaldo; Maria T. Mamba; Febe Marl G. Paat (International Journal of Evaluation and Research in Education (IJERE), 2021)
Guided by the lens of Bourdieu, this study examined the relationship of the students' economic capital (parents' monthly income and students' weekly allowance) and cultural capital (parents' highest educational attainment and students' community involvement) to their college readiness. The study utilized a descriptive-correlational design, and data were collected from 6,626 K-12 graduates enrolled in one state-university in Cagayan Valley Region, Philippines. The results reveal that the respondents have parents who have income below the Philippine poverty threshold level and have obtained a secondary level of education. They, too, are college-unready, implying that the competencies they obtained from their basic education need further enhancement. Moreover, economic and cultural capital becomes significant resources that are valuable in explaining the college readiness of Filipino Senior High School (SHS) graduates. Those who come from families with higher economic and cultural capital tend to have higher college readiness. Remarkably, the low economic and cultural capital of the students possibly explains their lack of college readiness. As they have less economic and cultural capital, they tend to have fewer competencies to capacitate them in hurdling tertiary education. Hence, these disadvantaged students generally struggle to achieve more and to be successful in life.